2022
DOI: 10.1186/s12905-022-01967-9
|View full text |Cite
|
Sign up to set email alerts
|

New Moms Wellness Study: the randomized controlled trial study protocol for an intervention study to increase fruit and vegetable intake and lower breast cancer risk through weekly counseling and supplemental fruit and vegetable box delivery in breastfeeding women

Abstract: Background Laboratory studies indicate that chemicals in fruits and vegetables have anti-carcinogenic and anti-inflammatory activities that can lower breast cancer risk. However, epidemiologic studies of the association between fruit and vegetable intake and breast cancer risk have produced mixed results. Measurement error, confounding, and an emphasis on diet in later adulthood may contribute to weak associations. This paper describes a randomized controlled diet intervention trial in breastfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Many xenobiotics promote the growth of human BC cells by inducing genetic modifications and epigenetic alterations, such as serum-derived estrogenic zeranol metabolites from industrial beef meat [ 295 ], as well as alcohol exposure [ 296 ]. Furthermore, a recent study highlighted an important correlation between fruit and vegetable consumption and the biomarkers of BC in lactating women, including weight, breast epithelial DNA methylation, and inflammation [ 297 ]. Taking into account that mammographic breast density is a recognized risk factor for BC, Pasta et al showed that the association comprising boswellic acid, betaine, and myo-inositol significantly reduced mammary density, with relevant clinical outcomes in BC prevention [ 298 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%
“…Many xenobiotics promote the growth of human BC cells by inducing genetic modifications and epigenetic alterations, such as serum-derived estrogenic zeranol metabolites from industrial beef meat [ 295 ], as well as alcohol exposure [ 296 ]. Furthermore, a recent study highlighted an important correlation between fruit and vegetable consumption and the biomarkers of BC in lactating women, including weight, breast epithelial DNA methylation, and inflammation [ 297 ]. Taking into account that mammographic breast density is a recognized risk factor for BC, Pasta et al showed that the association comprising boswellic acid, betaine, and myo-inositol significantly reduced mammary density, with relevant clinical outcomes in BC prevention [ 298 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%